The Ecxistence of Javanese Language Among Transmigrants in Tanjung Sari Hamlet, Melawi Regency - Vebianti, Popi; Firmansyah, Andang; Chalimi, Ika Rahmatika (Universitas Tanjungpura, 2025)
This research is to determine the existence of Javanese language among transmigrant communities in Tanjung Sari Hamlet. Based on qualitative phenomenology. The data source was transmigration actors, residents of transmigration descent, residents related to research The necessary information was gathered using a triangulation off technigues: observation, interviews,and doucumentation. Research techniques technique used data reduction, data presentation and conclusion drawing. The results of this study show that (1) the existence of the use of Javanese language in transmigrant communities in Tanjung Sari Hamlet, Nanga Pinoh Subdistrict, Melawi Regency shows results that lead to this collapse as seen from the high intensity of the use of Indonesian in daily life and the use of Javanese language is only limited to the family environment and the Javanese community (2) Factors inhibiting the existence of the use of Javanese language in transmigrant communities in Tanjung Sari Hamlet, Nanga Pinoh Subdistrict, Melawi Regency, parental educational background, The dominance of Indonesian language usage, the diverse nature of society, not taught in formal education and inter-ethnic marriage (3) the condition of the transmigrant community in Tanjung Sari Hamlet, Nanga Pinoh District, Melawi Regency the majority of transmigrant communities are farmers with crops and manage rubber plantations as a source of livelihood. The majority of transmigrants who came to this hamlet were people who participated in government programs, especially the transmigration program in 1983-1984.